Ectopic spinal calcification associated with diffuse idiopathic skeletal hyperostosis (DISH): A quantitative micro‐ct analysis. Issue 3 (28th February 2019) - Fournier, Dale E.; Norley, Chris J. D.; Pollmann, Steven I.; Bailey, Christopher S.; Al Helal, Fahad; Willmore, Katherine E.; Holdsworth, David W.; Dixon, S. Jeffrey; Séguin, Cheryle A.
ABSTRACT: Diffuse idiopathic skeletal hyperostosis (DISH) is a non‐inflammatory spondyloarthropathy identified radiographically by calcification of the ligaments and/or entheses along the anterolateral aspect of the vertebral column. The etiology and pathogenesis of calcifications are unknown, and the diagnosis of DISH is currently based on radiographic criteria associated with advanced disease. To characterize the features of calcifications associated with DISH, we used micro‐computed tomographic imaging to evaluate a cohort of 19 human cadaveric vertebral columns. Fifty‐three percent of the cohort ( n = 10; 3 females, 7 males, mean age of death = 81 years, range 67–94) met the radiographic criteria for DISH, with calcification of four or more contiguous vertebral segments. In almost all cases, the lower thoracic regions (T8‐12) were affected by calcifications, consisting primarily of large, horizontal outgrowths of bony material. In contrast, calcifications localized to the upper thoracic regions demonstrated variability in their presentation and were categorized as either "continuous vertical bands" or "discontinuous‐patchy" lesions. In addition to the variable morphology of the calcifications, our analysis demonstrated remarkable heterogeneity in the densities of calcifications, ranging from internal components below the density of cortical bone to regions of hyper‐dense material that exceeded cortical bone. These findings establish that the current radiographic criteria for DISH capture heterogeneous presentations of ectopic spine calcification that can be differentiated based on morphology and density. These findings may indicate a naturally heterogenous disease, potential stage(s) in the natural progression of DISH, or distinct pathologies of ectopic calcifications. © 2019 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res